Effects of runoff harvesting through semi-circular bund on some soil characteristics - M. Heshmati; M. Gheitury; M. Hosseini (Global Journal of Environmental Science and Management)
In this study, to investigate the effects of runoff harvesting on soil properties in the semiarid forest, runoff harvesting through semi-circular bund was considered as a method to conserve soil and thereby combat tree mortality. In order to evaluate this hypothesis, runoff was harvested through the semi-circular bund affecting soil quality and moisture storage. The selected forest site is located in Kalehzard, Kermanshah, in Zagros region of western Iran. The experiment was a randomized complete block design with four treatment plots: bund with protection, protection treatment, bund without protection and control treatment. The results showed that the mean values of soil organic carbon in the bund with protection, protection treatment, bund without protection and  control treatment were 2.35, 2.40, 1.90, and 1.80%, respectively, indicating no significant difference among them in the first year, while there were significant (p> 0.05) increases in the bund with protection and protection treatment after three years. Furthermore, coarse and very coarse soil aggregates increased significantly in the bund with protection treatment. This treatment also attributed to significant reduction in soil bulk density from 1.46 (in the first year) to 1.32 (in the third year), which enhanced soil moisture content. Finally it was found that bunds with protection significantly curtail dieback and adverse re-growing of stands due to the coupled effects of bund building and protection to curtail forest mortality in the semi-arid regions.